Asuhan Keperawatan Pada Tn.A Dengan Gangguan Sistem Pernafasan Luka Trakheostomi - Miftahul Jannah (Pusat Riset dan Inovasi Nasional, 2023)
Tracheostomy is the act of creating a stoma or hole so that air can enter the lungs by bypassing the upper airway. Tracheostomy can be performed as an operative procedure which aims to create a new airway in the trachea by making an incision or incision in the 2nd, 3rd, 4th tracheal rings. Case study design: The type of research used is a descriptive observational research design with a case study approach in patients diagnosed with respiratory system disorders, Tracheostomy wounds, namely a research design that includes an intensive study of one research unit: for example one patient, family group, group, or institution. Although the number of subjects tends to be small, the number of variables studied is very broad. The focus of this case study is